A method for treating lithium mica tailings
The separation of feldspar and quartz in lithium mica tailings is solved through high-gradient magnetic separation and flotation technology, and the problems of environmental pollution and safety hazards in tailings treatment are achieved, and the efficient and comprehensive utilization of lithium mica tailings resources are achieved.
Patent Information
- Application Number
- CN202211105711.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-09-10
AI Technical Summary
The existing technology is difficult to efficiently and quickly realize the comprehensive utilization and development of lithium mica tailings resources, resulting in pollution of tailings storage, occupying land, consuming management costs, and posing safety hazards.
Magnetization sorting was performed using a high-gradient magnetic separator, and then feldspar and quartz were separated by beating and flotation techniques, and finally photovoltaic feldspar powder and low iron high-purity quartz were obtained through drying packaging.
It has achieved efficient separation of medium-fesspar and quartz of lithium mica tailings, and obtained photovoltaic-grade high-quality fesspar powder and low-iron high-purity quartz with higher added value, solving the environmental pollution and safety hazards of tailings treatment.
Smart Images

Figure CN115625032B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of mineral engineering, and in particular to a method for treating lepidolite tailings. Background Art
[0002] In recent years, with the rapid development of new energy vehicles, Yichun, as China's largest lithium mica reserve base, has ushered in the rapid development of lithium mica mineral resources. Lithium mica ore is rich in tantalum, niobium, rubidium, cesium, tin and other rare metals. The potassium-sodium feldspar and quartz in the ore are high-quality ceramic and glass raw materials with high development and utilization value. The grade of lithium mica ore is between 0.2-1.2%. Generally, 10 tons of ore are required to float 1 ton of lithium mica concentrate, and 9 tons of lithium mica tailings will be produced. With the continuous construction and expansion of enterprises, it is estimated that there will be nearly 40 million tons of tailings per year in the future. According to the current tailings treatment method, large-scale storage not only pollutes the environment, occupies land, consumes management costs, but also poses great safety hazards. Therefore, how to efficiently and quickly realize the comprehensive utilization and development of lithium mica tailings resources has become a difficult problem at this stage. Summary of the invention
[0003] The main purpose of the present invention is to provide a method for treating lepidolite tailings, aiming to solve the above technical problems.
[0004] To achieve the above object, a method for treating lithium mica tailings proposed by the present invention comprises:
[0005] Step 1, sending the lithium mica tailings into a high gradient magnetic separator for magnetization separation to obtain magnetically separated tailings;
[0006] Step 2, the tailings obtained in step 1 after magnetic separation are sent to a pulping barrel, and water is added to the pulping barrel to adjust the solid content to 10-60%, and an alkaline aqueous solution is added to adjust the alkaline environment, and then the first flotation agent is added to the pulping barrel for pulping, and the slurry after pulping is pumped into a positive flotation machine for positive flotation to float out rough quartz, and the feldspar slurry in the positive flotation machine is separated into solid and liquid by a belt filter to obtain a section of feldspar;
[0007] Step 3, the rough quartz floated in step 1 is separated from the solid by a belt filter, and the separated rough quartz is sent to the second flotation beating barrel, and water is added to the beating barrel at the same time, and an acidic aqueous solution is added to form an acidic environment, and then the second flotation agent is added to the beating barrel for slurry adjustment, and the slurry adjusted material is pumped into the flotation machine of the second flotation for reverse flotation, and the foam from the second flotation enters the belt filter for liquid-solid separation, and the obtained solid is the second feldspar; the slurry from the second flotation is sent to the belt filter for liquid-solid separation, and the obtained solid is high-purity quartz.
[0008] In one embodiment, the step of adding an alkaline aqueous solution to create an alkaline environment comprises:
[0009] Add 1-30% alkaline aqueous solution to adjust the pH value to 9.5-13.5.
[0010] In one embodiment, the alkaline aqueous solution is a sodium hydroxide solution or a potassium hydroxide solution.
[0011] In one embodiment, the step of adding an acidic aqueous solution to create an acidic environment comprises:
[0012] An acidic aqueous solution with a concentration of 1-30% is added to adjust the pH to 1.5-4.5.
[0013] In one embodiment, the acidic aqueous solution is sodium sulfate or potassium sulfate.
[0014] In one embodiment, the formula mass ratio of the first flotation agent is: 30-90% of mixed amine, 0.3-35% of sodium acetate, 0.1-25% of sodium dihydrogen phosphate, and 0.5-35% of organic acid.
[0015] In one embodiment, the mixed amine of the first flotation agent includes cationic polyacrylamide, poly(diallyldimethylammonium chloride), melamine-formaldehyde resin, laurylamine, N-dodecylacetamide, polyamine, polydicyandiamide and any combination thereof.
[0016] In one embodiment, the formula weight ratio of the second flotation agent is 30-90% of mixed amine, 5-30% of diesel, 0.3-25% of aminotrimethylene phosphoric acid, and 0.3-25% of inorganic base.
[0017] In one embodiment, the mixed amine of the second flotation agent includes mixed amines including dodecyl ether amine, dodecyl ether amine, lauryl amine, tetradecyl amine, hexadecyl amine, oleyl amine, N-dodecyl acetamide, tetradecyl ether amine and any combination thereof.
[0018] In one embodiment, after step 3, the method for treating lithium mica tailings further comprises:
[0019] Drying and packaging the feldspar obtained in step 2 and step 3 to obtain photovoltaic grade feldspar powder;
[0020] The high-purity quartz obtained in step three is dried and packaged to obtain photovoltaic-grade low-iron high-purity quartz.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention can separate feldspar and quartz from lithium mica tailings respectively to obtain photovoltaic-grade high-quality feldspar powder and low-iron high-purity quartz with higher added value, wherein the purity of quartz is above 99.5%, Fe2O3 is less than 0.0030%, the whiteness of feldspar powder is greater than 80%, K+Na is greater than 10%, and Al2O3 is greater than 17%.
[0023] The invention has simple production process, low cost, stable product quality and is easy for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0025] Figure 1 The present invention is a schematic diagram of the process of treating lepidolite tailings according to an embodiment of the present invention.
[0026] Description of Figure Numbers:
[0027] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0030] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0031] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0032] The invention provides a method for treating lepidolite tailings.
[0033] like Figure 1 As shown, the lithium mica tailings processing method provided by the embodiment of the present invention includes the lithium mica tailings processing method including:
[0034] Step 1, sending the lithium mica tailings into a high gradient magnetic separator for magnetization separation to obtain magnetically separated tailings;
[0035] Step 2, the tailings obtained in step 1 after magnetic separation are sent to a pulping barrel, and water is added to the pulping barrel to adjust the solid content to 10-60%, and an alkaline aqueous solution is added to adjust the alkaline environment, and then the first flotation agent is added to the pulping barrel for pulping, and the slurry after pulping is pumped into a positive flotation machine for positive flotation to float out rough quartz, and the feldspar slurry in the positive flotation machine is separated into solid and liquid by a belt filter to obtain a section of feldspar;
[0036] Step 3, the rough quartz floated in step 1 is separated from the solid by a belt filter, and the separated rough quartz is sent to the second flotation beating barrel, and water is added to the beating barrel at the same time, and an acidic aqueous solution is added to form an acidic environment, and then the second flotation agent is added to the beating barrel for slurry adjustment, and the slurry adjusted material is pumped into the flotation machine of the second flotation for reverse flotation, and the foam from the second flotation enters the belt filter for liquid-solid separation, and the obtained solid is the second feldspar; the slurry from the second flotation is sent to the belt filter for liquid-solid separation, and the obtained solid is high-purity quartz.
[0037] Step 4: Dry and package the feldspar obtained in step 2 and step 3 to obtain photovoltaic grade feldspar powder;
[0038] The high-purity quartz obtained in step three is dried and packaged to obtain photovoltaic-grade low-iron high-purity quartz.
[0039] Through the above steps, feldspar and quartz in the lithium mica tailings can be separated respectively to obtain photovoltaic-grade high-quality feldspar powder and low-iron high-purity quartz with higher added value, wherein the purity of quartz is more than 99.5%, Fe2O3<0.0030%, the whiteness of feldspar powder is>80%, K+Na>10%, and Al2O3>17%.
[0040] Wherein, the step of adding an alkaline aqueous solution to form an alkaline environment comprises:
[0041] Add an alkaline aqueous solution with a concentration of 1-30% to adjust the pH value to 9.5-13.5, wherein the alkaline aqueous solution is a sodium hydroxide solution or a potassium hydroxide solution.
[0042] In one embodiment, the step of adding an acidic aqueous solution to create an acidic environment comprises:
[0043] An acidic aqueous solution with a concentration of 1-30% is added to adjust the pH to 1.5-4.5, wherein the acidic aqueous solution is sodium sulfate or potassium sulfate.
[0044] In one embodiment, the formula mass ratio of the first flotation agent is: 30-90% of mixed amine, 0.3-35% of sodium acetate, 0.1-25% of sodium dihydrogen phosphate, and 0.5-35% of organic acid.
[0045] Wherein, the mixed amine of the first flotation agent includes cationic polyacrylamide, poly(diallyldimethylammonium chloride), melamine-formaldehyde resin, laurylamine, N-dodecylacetamide, polyamine, polydicyandiamide and any combination thereof.
[0046] In addition, the formula weight ratio of the second flotation agent is 30-90% of mixed amine, 5-30% of diesel, 0.3-25% of aminotrimethylene phosphoric acid, and 0.3-25% of inorganic alkali.
[0047] Wherein, the mixed amine of the second flotation agent includes mixed amines including dodecyl ether amine, dodecyl ether amine, lauryl amine, tetradecyl amine, hexadecyl amine, oleyl amine, N-dodecyl acetamide, tetradecyl ether amine and any combination thereof.
[0048] Example 1
[0049] High gradient magnetic separation: The lithium mica tailings are fed into the raw material silo by a loader, and then conveyed to the transition silo by a belt. The tailings are accurately fed by a microelectronic belt scale, and then magnetically separated by a high gradient magnetic separator to remove the ferromagnetic substances adhering to the tailings, and the concentrate is obtained after magnetic separation.
[0050] First-stage flotation: the concentrate obtained after magnetic separation is sent to the beating barrel, and water is added to the beating barrel to adjust the slurry to 20% solid content, and 5% concentration of sodium hydroxide is added to adjust the pH value to 10.5, and then the first flotation agent is added to the slurry mixing barrel for slurry mixing. The slurry-mixed material is pumped into the positive flotation machine for positive flotation. The rough quartz floated out enters the next process, and the feldspar slurry in the positive flotation machine is separated from the solid and liquid by a belt filter to obtain the first-stage feldspar;
[0051] Secondary flotation: The rough quartz obtained by flotation is separated from the solid by a belt filter, and the separated rough quartz is sent to the secondary flotation beating barrel. At the same time, water is added to the beating barrel, and 5% sulfuric acid is added to adjust the pH to 2.5. Then the second flotation agent is added to the beating barrel to adjust the slurry. The adjusted material is pumped into the flotation machine of the secondary flotation for reverse flotation. The foam obtained by the secondary flotation enters the belt filter for liquid-solid separation, and the solid obtained is the secondary feldspar; the slurry of the secondary flotation is sent to the belt filter for liquid-solid separation, and the solid obtained is high-purity quartz.
[0052] Drying and packaging: drying and packaging the feldspar obtained in step 2) and step 3) to obtain photovoltaic-grade feldspar powder; drying and packaging the high-purity quartz obtained in step 3) to obtain photovoltaic-grade low-iron high-purity quartz.
[0053]
[0054] Table 1.1 Test results of feldspar and quartz products in Example 1
[0055] Example 2
[0056] High gradient magnetic separation: The lithium mica tailings are fed into the raw material silo by a loader, and then conveyed to the transition silo by a belt. The tailings are accurately fed by a microelectronic belt scale, and then magnetically separated by a high gradient magnetic separator to remove the ferromagnetic substances adhering to the tailings, and the concentrate is obtained after magnetic separation.
[0057] First-stage flotation: the concentrate obtained after magnetic separation is sent to the beating barrel, and water is added to the beating barrel to adjust the slurry to 30% solid content, and 10% sodium hydroxide is added to adjust the pH value to 11, and then the first flotation agent is added to the mixing barrel for slurry adjustment. The slurry-adjusted material is pumped into the positive flotation machine for positive flotation. The rough quartz floated out enters the next process, and the feldspar slurry in the positive flotation machine is separated into solid and liquid by a belt filter to obtain the first-stage feldspar;
[0058] Secondary flotation: The rough quartz obtained by flotation is separated from the solid by a belt filter, and the separated rough quartz is sent to the secondary flotation beating barrel. At the same time, water is added to the beating barrel, and 15% sulfuric acid is added to adjust the pH to 3. Then the second flotation agent is added to the beating barrel to adjust the slurry. The adjusted material is pumped into the flotation machine of the secondary flotation for reverse flotation. The foam obtained by the secondary flotation enters the belt filter for liquid-solid separation, and the solid obtained is the secondary feldspar; the slurry of the secondary flotation is sent to the belt filter for liquid-solid separation, and the solid obtained is high-purity quartz.
[0059] Drying and packaging: drying and packaging the feldspar obtained in step 2) and step 3) to obtain photovoltaic-grade feldspar powder; drying and packaging the high-purity quartz obtained in step 3) to obtain photovoltaic-grade low-iron high-purity quartz.
[0060]
[0061] Table 1.2 Test results of feldspar and quartz products in Example 2
[0062] Example 3
[0063] High gradient magnetic separation: The lithium mica tailings are fed into the raw material silo by a loader, and then conveyed to the transition silo by a belt. The tailings are accurately fed by a microelectronic belt scale, and then magnetically separated by a high gradient magnetic separator to remove the ferromagnetic substances adhering to the tailings, and the concentrate is obtained after magnetic separation.
[0064] First-stage flotation: the concentrate obtained after magnetic separation is sent to the beating barrel, and water is added to the beating barrel to adjust the slurry to 50% solid content, and 25% concentration of sodium hydroxide is added to adjust the pH value to 12, and then the first flotation agent is added to the slurry mixing barrel for slurry mixing. The slurry-mixed material is pumped into the positive flotation machine for positive flotation. The rough quartz floated out enters the next process, and the feldspar slurry in the positive flotation machine is separated from the solid and liquid by a belt filter to obtain the first-stage feldspar;
[0065] Secondary flotation: The rough quartz obtained by flotation is separated from the solid by a belt filter, and the separated rough quartz is sent to the secondary flotation beating barrel. At the same time, water is added to the beating barrel, and 25% sulfuric acid is added to adjust the pH to 3.5. Then the second flotation agent is added to the beating barrel to adjust the slurry. The adjusted material is pumped into the flotation machine of the secondary flotation for reverse flotation. The foam obtained by the secondary flotation enters the belt filter for liquid-solid separation, and the solid obtained is the secondary feldspar; the slurry of the secondary flotation is sent to the belt filter for liquid-solid separation, and the solid obtained is high-purity quartz.
[0066] Drying and packaging: drying and packaging the feldspar obtained in step 2) and step 3) to obtain photovoltaic-grade feldspar powder; drying and packaging the high-purity quartz obtained in step 3) to obtain photovoltaic-grade low-iron high-purity quartz.
[0067]
[0068] Table 1.3 Test results of feldspar and quartz products in Example 3
[0069] In summary, according to the treatment of multiple different embodiments, feldspar and quartz in lithium mica tailings can be separated respectively, and photovoltaic-grade high-quality feldspar powder and low-iron high-purity quartz with higher added value can be obtained, wherein the purity of quartz is above 99.5%, Fe2O3<0.0030%; the whiteness of feldspar powder is>80%, K+Na>10%, and Al2O3>17%.
[0070] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for treating lepidolite tailings, characterized in that: The method for treating lepidolite tailings comprises: Step 1, sending the lithium mica tailings into a high gradient magnetic separator for magnetization separation to obtain magnetically separated tailings; Step 2, the tailings obtained after magnetic separation in step 1 are sent to a pulping barrel, and water is added to the pulping barrel to adjust the solid content to 10-60%, and an alkaline aqueous solution with a concentration of 1-30% is added to adjust the pH value to 9.5-13.5, and then the first flotation agent is added to the pulping barrel for pulping, and the slurry after pulping is pumped into a positive flotation machine for positive flotation to float out rough quartz, and the feldspar slurry in the positive flotation machine is separated from the solid by a belt filter to obtain a section of feldspar, wherein the formula weight proportion of the first flotation agent is: 30-90% of mixed amine, 0.3-35% of sodium acetate, 0.1-25% of sodium dihydrogen phosphate, and 0.5-35% of organic acid; Step 3, the rough quartz floated in step 1 is separated from the solid by a belt filter, and the separated rough quartz is sent to the second flotation beating barrel, and water is added to the beating barrel at the same time, and an acidic aqueous solution with a concentration of 1-30% is added to adjust the pH to 1.5-4.5, and then the second flotation agent is added to the beating barrel for slurry adjustment, and the slurry-adjusted material is pumped into the flotation machine of the second flotation for reverse flotation, and the foam from the second flotation enters the belt filter for liquid-solid separation, and the solid obtained is the second feldspar; the slurry from the second flotation is sent to the belt filter for liquid-solid separation, and the solid obtained is high-purity quartz, wherein the formula mass proportion of the second flotation agent is 30-90% of mixed amine, 5-30% of diesel, 0.3-25% of aminotrimethylene phosphoric acid, and 0.3-25% of inorganic alkali.
2. The method for treating lepidolite tailings according to claim 1, wherein: The alkaline aqueous solution is a sodium hydroxide solution or a potassium hydroxide solution.
3. The method for treating lepidolite tailings according to claim 1, wherein: The acidic aqueous solution is sodium sulfate or potassium sulfate.
4. The method for treating lepidolite tailings according to claim 1, wherein: The mixed amine of the first flotation agent includes cationic polyacrylamide, poly(diallyldimethylammonium chloride), melamine-formaldehyde resin, laurylamine, N-dodecylacetamide, polyamine, polydicyandiamide and any combination thereof.
5. The method for treating lepidolite tailings according to claim 1, wherein: The mixed amine of the second flotation agent includes mixed amines including dodecyl ether amine, dodecyl ether amine, lauryl amine, tetradecyl amine, hexadecyl amine, oleyl amine, N-dodecyl acetamide, tetradecyl ether amine and any combination thereof.
6. The method for treating lepidolite tailings according to any one of claims 1 to 5, characterized in that: After step 3, the method for treating lithium mica tailings further comprises: Drying and packaging the feldspar obtained in step 2 and step 3 to obtain photovoltaic grade feldspar powder; The high-purity quartz obtained in step three is dried and packaged to obtain photovoltaic-grade low-iron high-purity quartz.
Citation Information
Patent Citations
Beneficiation method for producing quartz and feldspar by using river and lake sands
CN102824961A
Flotation agent for extracting quartz and feldspar of tailings
CN103084277A